That "Barton Fink Feeling” and the Fiery Furnace: The Book of Daniel and Joel and Ethan Coen's Barton Fink - Stefon, Matt (The journal of religion and film, 2008)
This paper explores the use of the Book of Daniel in Joel and Ethan Coen's Barton Fink. While some critics have noted the film's "apocalyptic” dimension, and have even mentioned the movie's two explicit mentions of the Daniel story, none has studied the close relationship between the biblical text and the film. This article argues that the Book of Daniel is central to the structure of Barton Fink, by arguing that the movie both presents the crisis of Barton's visionary attempt to deliver both a dream and its interpretation (Dan. 2:5), and offers an apocalyptic "cure” to correct his vision.